Performance investigation of a hybrid liquid-desiccant air conditioning system in a pharmaceutical warehouse: a case study and refined strategy - Huang, Li; Guan, Bowen; Qi, Meiwei; Liu, Yanbin; Yang, Haobo (Frontiers in Built Environment, 2024)
Liquid-desiccant-based air conditioning demonstrates significant potential for energy conservation and emission reduction in industrial building applications, contributing to the advancement of a cleaner industrial future. In this study, the on-site performance of a hybrid liquid-desiccant air conditioning system installed in a pharmaceutical warehouse was assessed. The results revealed that blind use of the liquid desiccant caused considerable heat–cold offset in the system, which badly restricted its energy performance. Under the basic conditions, only 81.8% of the total cooling capacity provided by the system could be obtained through the return air, while the remaining 18.2% was wasted owing to the considerable heat–cold offset. A refined system was then proposed to improve the system energy performance. By avoiding the heat–cold offset, the coefficient of performance could be improved from 2.2–2.4 to 2.9–3.1. Moreover, an electricity savings rate of 20.2% was achieved with the refined system over the duration of the entire cooling season. Hence, this work provides valuable insights into energy conservation and emission reduction in industrial air conditioning systems, supporting the process of industrial decarbonization.